Urgent-Start Peritoneal Dialysis: The First Year of Brazilian Experience - Bitencourt Dias, Dayana [UNESP] (2017)
Background: This study aimed to evaluate mechanical and infectious complications associated with urgent-start peritoneal dialysis (PD) and patients and technique survival in the first 180 days. Methods: It was a prospective study that evaluated chronic patients who started unplanned PD using high-volume PD (HVPD) right after (<72 h) PD catheter placement. After hospital discharge, patients were treated with intermittent PD on alternate days in a dialysis unit until family training was provided. Results: Fifty-one patients fulfilling the following criteria were included: age was 62.1 ± 15 years, with diabetes as the main etiology of end-stage renal disease (39%), and uremia as the main dialysis indication (76%). Metabolic and fluid controls were achieved after 3 sessions of HVPD, and patients remained in intermittent PD for 23.2 ± 7.2 days. Mechanical complications occurred in 25.7% and peritonitis rate was 0.5 episode/patient-year. In the first 6 months, technique and patients survival rates were 86 and 82.4% respectively. Conclusion: The PD modality was a feasible and safe alternative to hemodialysis in the urgent-start dialysis.